Perancangan Booth Pameran Event Sido Muncul dengan Menampilkan Produk-Produk Indonesia - Jihan Namira; Teguh Imanto (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Sido event exhibition is an event aimed at introducing Indonesian products to the community. In a design booth of this exhibition, the focus given to the promotion of a major product Sido appeared cool cider from various industrial sectors. With designs done to create interesting looks, reflect Indonesian identity, and provide a memorable experience for visitors. In addition to promotion, the exhibition becomes a container for building networks on businesses and exchanging information between business operators. This emerging Sido exhibition booth is one of the media that will showcase the products of the Sido appear and become one of the main products used is the product of a cool ready-to-drink Sarang Sari drink. So that the public can get to know more about the main product of the cool sarang drink.